1985
DOI: 10.1016/0012-821x(85)90085-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical diffusion of fluorine in melts in the system Na2OAl2O3SiO2

Abstract: The volatilization of fluorine from three melts in the system Na20-A1203-SiO 2 has been investigated at 1 atm pressure and 1200-1400°C. The melts chosen have base compositions corresponding to albite, jadeite and a peraluminous melt with 75 mole % SiO 2. Melt spheres were suspended from platinum loops in a vertical tube furnace in a flow of oxygen gas, then quenched, sectioned and analysed by electron microprobe. The microprobe scans indicate that transport of fluorine to the melt-vapor interface is by binary,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…4). However, Dingwell and Scarfe (1985) observed a 6-fold increase in F diffusivity between 1 atm and 1.0 GPa in jadeitic melt, whereas our measurements on a basaltic melt yield a decrease of only 1.1, which is within our inter-experimental variability. The differing influence of pressure on F diffusion in jadeitic melt and in basaltic melt is possibly due to the difference in experimental techniques used in this study and in Scarfe (1984, 1985), where their 1 atm experiments involved the loss of F, Si, Al and Na from the melt by vaporization, potentially creating a much greater chemical potential gradient than in our study.…”
Section: Halogen Diffusion In Different Melt Compositionssupporting
confidence: 65%
See 2 more Smart Citations
“…4). However, Dingwell and Scarfe (1985) observed a 6-fold increase in F diffusivity between 1 atm and 1.0 GPa in jadeitic melt, whereas our measurements on a basaltic melt yield a decrease of only 1.1, which is within our inter-experimental variability. The differing influence of pressure on F diffusion in jadeitic melt and in basaltic melt is possibly due to the difference in experimental techniques used in this study and in Scarfe (1984, 1985), where their 1 atm experiments involved the loss of F, Si, Al and Na from the melt by vaporization, potentially creating a much greater chemical potential gradient than in our study.…”
Section: Halogen Diffusion In Different Melt Compositionssupporting
confidence: 65%
“…Nevertheless, comparison between our results and those of Dingwell and Scarfe suggests that any pressure affect on F diffusion in basaltic melts between 1 atm and 0.5 GPa will be small. Dingwell and Scarfe's (1985) measurements of F diffusion in albite melt at 1 atm indicate that its diffusivity is about two orders of magnitude lower than in jadeite and in basalt (Fig. 4) at 1.0 GPa, and there is about 1 order of magnitude difference between F diffusion in jadeitic and albitic melts at 1 atm.…”
Section: Halogen Diffusion In Different Melt Compositionsmentioning
confidence: 83%
See 1 more Smart Citation
“…The second contribution of the above authors to the data base on chemical diffusion of fluorine (Dingwell and Scarfe, 1985) involved I-atmosphere devolatilization experiments. Fluorine-enriched spheres of albite, jadeite, and peraluminous glass (75 wt% Si0 2 ) were suspended from Pt loops in an oxygen-flow furnace, such that at high temperature (1200 to 1400°C) the fluorine in the spheres exchanged with ambient oxygen.…”
Section: Crystal Dissolutionmentioning
confidence: 99%
“…Hermann et al (1987) suggest diffusion coefficients for C1 will be several orders of magnitude larger than those for F; however, their C1 data are suspect due to the high measured C1 solubility, the peculiar pressure dependence, and the use of Cl, gas. Dingwell and Scarfe (1985) measured F diffusion in three anhydrous Na,O-Al,O,-SiO, melts; a tenuous extrapolation of data for their "albite" composition to 400°C yields D = l@13 cm2/sec, but there was a strong dependence on glass composition in this limited set of experiments, suggesting the need to obtain data for compositions that more closely match the BRT glasses. Jambon (1982) measured diffusion coefficients for a variety of cations in obsidian glasses and melts, and concluded that the activation energies were largely dependent on the squared formal charge and the ionic radius.…”
Section: Gas Transport Experimentsmentioning
confidence: 91%